1985
DOI: 10.1042/bj2280103
|View full text |Cite
|
Sign up to set email alerts
|

A method to quantify glucose utilization in vivo in skeletal muscle and white adipose tissue of the anaesthetized rat

Abstract: A quantitative method allowing determination of glucose metabolism in vivo in muscles and white adipose tissue of the anaesthetized rat is presented. A tracer dose of 2-deoxy[3H]glucose was injected intravenously in an anaesthetized rat and the concentration of 2-deoxy[3H]glucose was monitored in arterial blood. After 30-80 min, three muscles, the soleus, the extensor digitorum longus and the epitrochlearis, periovarian white adipose tissue and brain were sampled and analysed for their content of 2-deoxy[3H]gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
268
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(275 citation statements)
references
References 26 publications
6
268
1
Order By: Relevance
“…Skeletal muscle (gastrocnemius and quadriceps) samples were removed 30 min after injection. The glucose utilisation index was determined by measuring the accumulation of radiolabelled compounds [34]. The amount of 2-DG-6-phosphate/mg protein was divided by the integral of the concentration ratio of 2-DG to unlabelled glucose measured.…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal muscle (gastrocnemius and quadriceps) samples were removed 30 min after injection. The glucose utilisation index was determined by measuring the accumulation of radiolabelled compounds [34]. The amount of 2-DG-6-phosphate/mg protein was divided by the integral of the concentration ratio of 2-DG to unlabelled glucose measured.…”
Section: Methodsmentioning
confidence: 99%
“…This was determined by the method of Ferre et al (1985) and found to be 0.46 in NMRI mice (Mahony and Tisdale, 1990). …”
Section: Glucose Utilization In Vivomentioning
confidence: 99%
“…The correction factor for the discrimination against 2-deoxyglucose (lumped constant) does not vary with changes in glucose utilisation rates of white and brown adipose tissue, and thus the use of the GUI value gives an accurate estimation of differences between groups. 22 Conditions were near steady state with coef®cients of variance of blood glucose over the 1 h period of sampling of`15%.…”
Section: Glucose Utilisation In Vivomentioning
confidence: 99%
“…Rates of glucose uptakeaphosphorylation by adipose tissue in vivo were estimated from rates of uptake and phosphorylation of 2-deoxy[1-3 H]-D-glucose (Amersham Interanational, Amersham, Bucks, UK) 22 in unstressed conscious rats. 23 Each rat was ®tted with an indwelling cannula for injection and sampling as described in Ref.…”
Section: Glucose Utilisation In Vivomentioning
confidence: 99%